1966
DOI: 10.1111/j.1474-919x.1966.tb07205.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration Across the Mediterranean Observed by Radar

Abstract: SUMMARY Bird migration across the Mediterranean was studied by radar from an aircraft carrier for brief periods during the springs of 1961, 1962 and 1963 and in the autumn of 1963. The radar displays were photographed and analysed to give intensity (scales 0 to 6) and tracks have been plotted on the accompanying Maps together with Tables setting out the weather data and records of bird sightings. Most echoes that could be measured were between 4,000 and 6,000 ft. Small (passerine) echoes usually moved at 20–30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…In spring passerines are concentrated in the northern and north-eastern part of Egypt for stopover just before crossing the second barrier (the Mediterranean Sea). This is consistent with Casement (1966), who suggested that passerines performed an intermittent migration strategy, which was also reported by Biebach et al (2000), Schmaljohann et al (2007) and Salewski et al (2009).…”
Section: Migration Intensitysupporting
confidence: 80%
“…In spring passerines are concentrated in the northern and north-eastern part of Egypt for stopover just before crossing the second barrier (the Mediterranean Sea). This is consistent with Casement (1966), who suggested that passerines performed an intermittent migration strategy, which was also reported by Biebach et al (2000), Schmaljohann et al (2007) and Salewski et al (2009).…”
Section: Migration Intensitysupporting
confidence: 80%
“…Ringing recoveries are in general more abundant along the western route, but this could be influenced by re‐encounter probabilities (Procházka et al ). Local radar observations (Casement , Bruderer and Liechti ) have also shown a non‐uniform distribution of nocturnal migrants over the Mediterranean, with larger concentrations in both the western and eastern parts of the region. The Alps also play a role in shaping such a pattern of spatial distribution (Bruderer and Jenni , Liechti et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It allows us to estimate flying time and hence distance that migrants cover during a single night. Numerous radar studies in the 1960s and 1970s showed that nocturnal migration of passerines started soon after sunset (Lack 1960(Lack , 1963Drury and Nisbet 1964;Casement 1966;Parslow 1968;Gauthreaux Jr 1971;Lindgren and Nilsson 1975;Alerstam 1976;Richardson 1978a). As migration intensity on radar screens soon reached a peak, it was assumed that the main take-off period was restricted to a short twilight period.…”
Section: Introductionmentioning
confidence: 97%